1962
DOI: 10.1126/science.136.3517.710
|View full text |Cite
|
Sign up to set email alerts
|

A Protozoon (Dileptus; Ciliata) Predatory upon Metazoa

Abstract: Dileptus, a common holotrich, may function as a predator upon a variety of metazoan animals representing such varied phyla as Cnidaria, Platyhelminthes, Aschelminthes, Annelida, and Mollusca. Very young animals and wounded animals are especially vulnerable. Effective predation is directly related to the concentration of Dileptus to which the victim is exposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Systematics used are those of Lynn & Small (2000). Feeding types are the particle size-class grazed (pico-, nano-or microplanktonic) and whether the ciliates are primarily interception or filter feeders, based on literature summarized by Foissner et al (1999) as well as specialized literature (Brown & Jenkins 1962, Jonsson 1986, Müller 1991, Kivi & Setälä 1995, 2imek et al 1995, Kenter et al 1996, Jürgens & 2imek 2000, Weisse et al 2001. R 2 values are the proportion shared variance between the species and either the cluster to which they belong, or the cluster where the R 2 value is the next highest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Systematics used are those of Lynn & Small (2000). Feeding types are the particle size-class grazed (pico-, nano-or microplanktonic) and whether the ciliates are primarily interception or filter feeders, based on literature summarized by Foissner et al (1999) as well as specialized literature (Brown & Jenkins 1962, Jonsson 1986, Müller 1991, Kivi & Setälä 1995, 2imek et al 1995, Kenter et al 1996, Jürgens & 2imek 2000, Weisse et al 2001. R 2 values are the proportion shared variance between the species and either the cluster to which they belong, or the cluster where the R 2 value is the next highest.…”
mentioning
confidence: 99%
“…They could presumably counterbalance effects arising from P-depleted algae (Hochstädter 2000) by bacterivory and experience less grazing pressure owing to reduced daphnid biomass. The largest size class (>100 µm), as well as Clusters 1 and 9 (made up of ciliates such as Lacrymaria, Paradileptus and Dileptus), while in part algivorous, are also predacious, feeding on other ciliates, rotifers 258 Gaedke & Wickham: Seasonal and long-term dynamics of ciliates and large algae (Brown & Jenkins 1962, Foissner et al 1999. They were, therefore, less likely to be competitors with, or prey of, cladocerans, and in fact, with the exception of July, had weak or no correlations with cladoceran biomass.…”
mentioning
confidence: 99%
“…Since previous laboratory and field studies have shown the incidence of predation on triclads to be highly variable and dependent on the type of predator (Jennings, 1957 ;Brown & Jenkins, 1962;Young & Reynoldson, 1965 ;Davies, 1969 ;Davies & Reynoldson, 1971;Coward & Piedilato, 1972 ;Wright, 1975 ;Beveridge, 1982), the proposition that rhabdoids generally act as anti-predator devices by being distasteful must be seriously questioned .…”
Section: Discussionmentioning
confidence: 99%
“…Damselfly and dragonfly nymphs appear to be the only predators of any importance (Young and Reynoldson, 1965). Young Dugesia, however, may be attacked and consumed by the protozoan Dileptus if the concentration of the latter is high (Brown and Jenkins, 1962).…”
Section: Nutritionmentioning
confidence: 99%